Perception of the Expression of Learning Dimensions of Primary School Teachers at Workplace - Bakutytė, Rima; Ušeckienė, Lidija (Pedagogika, 2016)
In the context of global society since the 20th century the learning process at work has become especially urgent as on one hand it determines a person’s professional development, on the other hand it gives positive impetus to the development of the organization. This acknowledgement is supported by the theories of adult education shaping general attitude to learning in the environment and from the environment, the theories which place emphasis on how adults learn in general including teachers, and the empirical research at teachers’ workplaces. The aim of the research conducted with 151 Lithuanian primary school teachers is to reflect the dimensions of primary school teachers’ learning process at workplace and their perception, considering the dependence of the phenomena on age, work experience, education, obtained category of qualification and work satisfaction. The following research methods were applied during the research: analysis of scientific literature, questionnaires for teachers, method of mathematical statistics. The results of the research disclosed that: teachers’ learning at workplace is pretty much an important factor influencing their professional development positively. The development and dispersion of this phenomenon depend on external factors, but mainly on the individual’s readiness to learn not only watching and analysing their colleagues’ activities, but participating in work groups, etc. The learning process of primary school teachers at work can be described by these dimensions and their indicators: obtaining information, accumulation and dispersion of information, analysis of teaching activities, development of teaching activities and competence development. The results of empirical research revealed that the respondents admit, that the processes of obtaining information, accumulating and dispersing it operate smoothly, though they themselves rarely perform the analysis and edification of their teaching activities. The major problem is the refinement of their competences. It is deduced that the evaluation of learning dimensions at work by the teachers under consideration was meanly influenced by their age, work experience, education, obtained qualification category or satisfaction of professional activities.